2002
DOI: 10.1016/s1470-0328(02)01058-3
|View full text |Cite
|
Sign up to set email alerts
|

Grandmultiparae in a modern setting

Abstract: Objective To compare the incidence of antenatal and intrapartum complications and neonatal outcomes among women who had previously delivered five or more times (grandmultiparous) with that of agematched control women who had previously delivered two or three times (multiparous). Design A matched cohort study.Setting An inner city university maternity hospital in the United Kingdom.Sample Three hundred and ninety-seven grandmultiparous women were compared with three hundred and ninety-seven age-matched multipar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 10 publications
4
24
1
Order By: Relevance
“…While many antenatal and intrapartum complications like diabetes (overt and gestational), anemia, preterm delivery, malpresentation at term, postpartum hemorrhage, macrosomia showed a significant linear increase with increasing parity as indicated by v 2 test for linear trend (Fig. 1) as also reported by many other studies [3][4][5][6][7][8][9]; there were some, like the need for labor augmentation with its attendant risks specially in women of higher parity and soft tissue injuries, which showed a significantly declining trend with increasing parity as indicated by v 2 test for linear trend (Fig. 2).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…While many antenatal and intrapartum complications like diabetes (overt and gestational), anemia, preterm delivery, malpresentation at term, postpartum hemorrhage, macrosomia showed a significant linear increase with increasing parity as indicated by v 2 test for linear trend (Fig. 1) as also reported by many other studies [3][4][5][6][7][8][9]; there were some, like the need for labor augmentation with its attendant risks specially in women of higher parity and soft tissue injuries, which showed a significantly declining trend with increasing parity as indicated by v 2 test for linear trend (Fig. 2).…”
Section: Discussionsupporting
confidence: 77%
“…Bethel Solomon's concerns as expressed in his article ''The dangerous multipara'' in 1934 were found to be genuine about the risks associated with grand multiparity [7]. The risks definitely exist in women of grand multiparity, but it might be unreasonable to attribute all the risks to parity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The International Federation of Gynaecology and Obstetrics (1993) define grand multiparity as delivery of the fifth to ninth infant, whereas delivery of the ten (or more) are considered being greatgrandmultiparas. 7 Solomon's pointed out that maternal mortality was higher in grand multipara, which number increased steadily as parity became greater.…”
mentioning
confidence: 99%
“…9 However, there is still controversy as some studies reported that grand multiparous women don't have an increased incidence of obstetric complications particularly in developed countries where there is satisfactory health care conditions. 7,11 During the last few decades the proportion of grand multipara has decreased in most developed countries because of a dramatic change in the practice of contraception and the acceptance of family planning methods. 6 In present set, up grand multiparity is associated with increased likelihood of maternal and perinatal complications.…”
mentioning
confidence: 99%